A context-aware ubiquitous learning environment for language listening and speaking - Liu, T.-Y. (Journal of computer assisted learning, 2009)
This paper reported the results of a study that aimed to construct a sensor and handheld augmented reality (AR)‐supported ubiquitous learning (u‐learning) environment called the Handheld English Language Learning Organization (HELLO), which is geared towards enhancing students' language learning. The HELLO integrates sensors, AR, ubiquitous computing and information technologies. It is composed of two subsystems: an English learning management system and a u‐learning tool. In order to evaluate the effects of the proposed learning environment on the learning performance of students, a case study on English learning was conducted on a school campus. The participants included high school teachers and students. A learning course entitled ‘My Campus’ was conducted in the class; it included three activities, namely ‘Campus Environment’, ‘Campus Life’ and ‘Campus Story’. The evaluation results showed that the proposed HELLO and the learning activities could improve the students' English listening and speaking skills.